#Occupy Wall Street: Exploring Informal Learning About a Social Movement on Twitter. (July 2013) - Gleason, Benjamin
Recent events suggest that social media, also called web 2.0, can support mass social change. Although some critics have lamented how social media are eroding people's ability to communicate, others have argued that social media may allow individuals to leverage their individual voices against authoritarian leaders. This article seeks to understand the ways in which individuals can use a particular social media platform, the microblog Twitter, to learn about the Occupy Wall Street movement. This article uses a mixed-methods approach, incorporating descriptive statistics, content analysis, and a case study of the author's learning process to examine the existence of informal learning about the Occupy Wall Street movement. Scholars have proposed that informal learning about a social movement is associated with participation in the movement. This study suggests that Twitter supports multiple opportunities for participation in the Occupy movement—from creating, tagging, and sharing content to reading, watching, and following a hashtag—which may facilitate learners becoming more informed, engaged citizens. To help ground this discussion, an overview of the particular social and technical features of Twitter is provided. Second, several key learning theories that seem particularly synergistic with the affordances outlined and a review of the current state of research on learning within Twitter are described. Third, research questions, methods, and findings are presented, and a discussion that describes the implications for civic engagement in the democratic process is included.